RELATIVE EFFECTIVENESS OF GOOGLE CLASSROOM AND WHATSAPP INSTRUCTIONS ON STUDENTS’ ENGAGEMENT IN BASIC BIOLOGY IN UNIVERSITIES IN SOUTH-EAST, NIGERIA - Geoffrey Ukala; Nwanneka Josephine Okoli (MOJES: Malaysian Online Journal of Educational Sciences, 2025)
The relative effectiveness of Google Classroom (GC) and WhatsApp (WSP) instructions on students’ engagement in basic Biology in universities in South-East, Nigeria was examined. Two research questions and three null hypotheses were posed. A quasi-experimental, specifically nonrandomized, pretest-posttest comparison design was employed. The population comprised 252 first-year Biology education students admitted for the 2023/2024 academic session in federal universities in South-East, while the sample comprised 118 (36 male and 82 female) students purposively sampled from two universities. An adapted questionnaire titled Biology Education Student Academic Engagement Questionnaire (BESAEQ) was used. BESAEQ was duly validated by three professionals, trial tested and yielded internal consistency of 0.87, using tau-equivalent reliability. Research questions were answered using mean and standard deviation, while the null hypotheses were tested using Analysis of Covariance (ANCOVA) at a 0.05 level of significance. Results showed that undergraduates trained via GC instruction had an improved average engagement score compared to those trained with WSP instruction. Male undergraduates showed improved engagement compared to females, and gender was found to influence students’ academic engagement significantly. Furthermore, no interaction effect was found between gender and methods of instruction on undergraduates’ average engagement. Thus, it was recommended that lecturers should adopt a structured teaching platform like GC for effective instruction delivery in their classroom, with its collaborative and peer-driven interactions feature to enhance student engagement.